2017
DOI: 10.1242/jeb.146969
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in activity by noxious chemical stimulation is ameliorated by immersion in analgesic drugs in zebrafish

Abstract: Research has recently demonstrated that larval zebrafish show similar molecular responses to nociception to those of adults. Our study explored whether unprotected larval zebrafish exhibited altered behaviour after exposure to noxious chemicals and screened a range of analgesic drugs to determine their efficacy to reduce these responses. This approach aimed to validate larval zebrafish as a reliable replacement for adults as well as providing a high-throughput means of analysing behavioural responses. Zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 51 publications
0
81
0
1
Order By: Relevance
“…In contrast to and , Lopez-Luna et al (2017) considered reduced (not increased) activity as evidence of 'alleged pain behavior' in zebrafish exposed to 0.1-0.25% acetic acid. interpreted increased activity and cyclooxygenase-2 gene expression as evidence of nociception in larval zebrafish immersed in 0.0025-0.025% acetic acid.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to and , Lopez-Luna et al (2017) considered reduced (not increased) activity as evidence of 'alleged pain behavior' in zebrafish exposed to 0.1-0.25% acetic acid. interpreted increased activity and cyclooxygenase-2 gene expression as evidence of nociception in larval zebrafish immersed in 0.0025-0.025% acetic acid.…”
mentioning
confidence: 99%
“…
Lopez -Luna et al (2017) observed behavioral responses of larval zebrafish (Danio rerio) exposed for 10 min to pH 2.6-3.6 when acetic acid (0.01-0.25%) or citric acid (0.1-5%) was added to the tank water in the presence or absence of aspirin (1-2.5 mg l −1 ), morphine sulfate (1-48 mg l −1 ), lidocaine (1-5 mg l −1 ) and flunixin (8-20 mg l −1 ). Fish exposed to 0.1-0.25% acetic acid were less active than controls while those exposed to citric acid and 0.01% acetic acid were more active.
…”
mentioning
confidence: 99%
See 3 more Smart Citations